Agronomic performance of maize (Zea mays L.) genotypes under Azospirillum brasilense application and mineral fertilization - Tilhaqui Bertasello, Luiz Eduardo [UNESP]; Filla, Vinicius Augusto [UNESP]; Coelho, Anderson Prates [UNESP]; Moro, Gustavo Vitti [UNESP] (Univ Nacional Cuyo, Fac Ciencias Agrarias, 2021)
Maize has a high nitrogen (N) demand; as a result, more sustainable alternatives are needed to reduce demand for mineral fertilizers. The hypothesis is that the agronomic performance of maize genotypes diverges in their potential when subjected to different supplies of N. This study aimed to evaluate and characterize the agronomic performance of maize genotypes submitted to topdressing nitrogen fertilization and inoculation with Azospirillum brasilense and select the best genotypes within each management. An experiment was conducted in the second season of 2017, in jaboticabal-SP (Brazil), using 48 maize genotypes in a randomized block design. Treatments consisted of: 1) application of 140 kg ha(-1) nitrogen, using urea as mineral fertilizer; 2) A. brasilense inoculation via soil, at a rate of 600 mL ha(-1), as biological fertilization. Grain yield and agronomic traits were evaluated. The data were subjected to analysis of variance (F-Test), means were compared by Scott-Knott test at 5% probability, and multivariate statistical analysis was performed by principal component analysis. The maize genotypes showed contrasting agronomic performance in relation to the nitrogen supplies evaluated. Inoculation with A. brasilense via soil has a significant effect on increasing maize grain yield, making it a viable and more sustainable alternative in the supply of N. The choice of the genotype is an essential factor for the successful use of mineral nitrogen fertilization or A. brasiliense inoculation.
Keywords: diazotrophic bacteria; grain yield; biological nitrogen fixation; nitrogen